ASSOCIATION BETWEEN IRON DEFICIENCY ANEMIA AND FEBRILE SEIZURES - Khan, Shazia Aurangzaib; Salahuddin, Abid; Ali Noman, Mohammad (Journal of Postgraduate Medical Institute, 2016)
Objective: To find out the association between iron deficiency anemia and the frequency of first febrile seizure. Methodology: It was a comparative study conducted at Pediatric Medicine, Kuwait Teaching Hospital Peshawar and Hayatabad Medical Complex Peshawar from January 2015 to December 2015 in which a total of 160 patients were observed by taking 80 participants each in group A and group B respectively. Children in Group A were having febrile seizures while those in Group B were febrile but not having seizures. Results: The mean age of group A was 25±1.28 months while that of group B was 24±1.26 months. Frequency of Iron deficiency in group A was 38% while that in group B was 20% with a p value of 0.003. Conclusion: Febrile seizures were twice as common in children having iron deficiency anemia as compared to those who did not have iron deficiency anemia.